2017
DOI: 10.1002/ghg.1744
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different fluids on microcrack propagation in sandstone under true triaxial loading conditions

Abstract: The mechanical behavior of rock under conditions of multiphase fluids is currently a key scientific issue in the field of geotechnical engineering. In this work, we conducted triaxial compression experiments of initially water‐saturated samples, which were flooded with CO2 using the semipermeable separator method; comparatively investigated the mechanical behaviors of sandstone under the conditions of mono‐phase fluids CO2/N2/H2O and biphase fluid CO2‐H2O; and analyzed the stress‐strain characteristics, intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…We have already used the same cores to study the influence of the intermediate principal stress (σ 2 ) on the permeability evolution during true triaxial compression [41]. Although this paper emphasizes the effect of confining pressure (P c ) on the strain-permeability behavior of mudstone, which can be tested by a conventional triaxial apparatus with a cylindrical specimen, the true triaxial apparatus for rocks [41][42][43][44][45] at the Institute of Rock and Soil Mechanics, Chinese Academy of Sciences, which can exert three stresses independently, was still employed in this study because the specimen usually failed with a relatively flat fault parallel to σ 2 [42,[46][47][48]; the flow in the σ 2 direction can still be regarded as a one-dimensional flow. In contrast, the fault of the specimen in the CTC is not only very rough but also oblique to the flow direction [40,49] and the fluid flow inside the specimen near or after failure cannot be approximated as a one-dimensional flow; therefore, the cores in this study were also processed into cuboid specimens of 5 cm square by 10 cm long ( Figure 1) and the permeability in the σ 2 direction was monitored during deviatoric loading.…”
Section: Specimen Apparatus and Experimental Proceduresmentioning
confidence: 99%
“…We have already used the same cores to study the influence of the intermediate principal stress (σ 2 ) on the permeability evolution during true triaxial compression [41]. Although this paper emphasizes the effect of confining pressure (P c ) on the strain-permeability behavior of mudstone, which can be tested by a conventional triaxial apparatus with a cylindrical specimen, the true triaxial apparatus for rocks [41][42][43][44][45] at the Institute of Rock and Soil Mechanics, Chinese Academy of Sciences, which can exert three stresses independently, was still employed in this study because the specimen usually failed with a relatively flat fault parallel to σ 2 [42,[46][47][48]; the flow in the σ 2 direction can still be regarded as a one-dimensional flow. In contrast, the fault of the specimen in the CTC is not only very rough but also oblique to the flow direction [40,49] and the fluid flow inside the specimen near or after failure cannot be approximated as a one-dimensional flow; therefore, the cores in this study were also processed into cuboid specimens of 5 cm square by 10 cm long ( Figure 1) and the permeability in the σ 2 direction was monitored during deviatoric loading.…”
Section: Specimen Apparatus and Experimental Proceduresmentioning
confidence: 99%
“…The observed effects may be extended to the compaction creep of sandstones, when subcritical crack growth controls deformation. Previous workers have shown that microcracking is an important mechanism in sandstone deformation high stresses and strains (Heap et al, ; J. Zhang et al, ) and the presence of water leads to a pronounced weakening effect (Baud et al, ; Hu et al, , ). This suggests that, compared to the behavior of quartz sands, sandstones respond similarly to changes in water content and solution pH and presumably to the introduction of additives such as those studied here.…”
Section: Discussionmentioning
confidence: 99%
“…The effective shear stress is a dominant factor in controlling crack initiation and expansion within the rock. ,, During the triaxial compression test, the effective shear stress τ eff can be expressed as follows τ normale normalf normalf = false( σ 1 σ 3 false) 2 cos nobreak0em0.25em⁡ φ tan nobreak0em0.25em⁡ φ ( σ 1 + σ 3 ) 2 + α .25em tan nobreak0em0.25em⁡ φ P w where φ is the internal friction angle of rock …”
Section: Establishment Of the Permeability Modelmentioning
confidence: 99%
“…The permeability characteristics of rock determine the efficiency of engineering operations and long-term stability of rock infrastructures in the process of oil/gas exploitation, , geothermal energy extraction, , carbon dioxide storage, water-rich ore mining, and nuclear waste disposal. , For example, reservoirs are gradually depleted owing to the exploitation of oil/gas. During reservoir depletion, , the pore pressure ( p w ) and effective stress inside the reservoir rock decrease and increase respectively, resulting in decreased reservoir rock permeability and exploitation efficiency .…”
Section: Introductionmentioning
confidence: 99%